Weak lensing analysis of the galaxy clusterRX J1117.4+0743 ([VMF 98] 097) - Gonzalez, Elizabeth Johana (2014)
We present a weak lensing analysis of the galaxy clusterRX J1117.4+0743 ([VMF 98] 097) at z=0.485, based on data collectedwith Gemini South Telescope. The cluster was formerly analyzed byCarrasco et al. (2007, ApJ, 664, 777), and they found a large discrep-ancy between the mass estimated from Xray observations and lensingestimates, exceeding the X-ray mass by more than a factor three. Ourresult for the mass from the weak lensing analysis is lower than the massobtained by Carrasco et al. and closer to the X-ray mass.